An analysis of the business response to HIV/AIDS in the catering industry in Zimbabwe : a case study for organisations affiliated to the National Employment Council for the catering industry - Zhira, Pardon (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.